Aspectos quantitativos da deposição de gotas de pulverização em plantas de amendoim e Brachiaria plantaginea - Rodrigues-Costa, A. C.P.; Martins, D. [UNESP]; Costa, N. V.; Pereira, M. R.R. [UNESP] (FapUNIFESP (SciELO), 2012)
The objective of this study was to evaluate the amount of spray deposition on peanut plants (Aracahis hypogaea) and on the weed Brachiaria plantaginea, in the rows and inter rows of the culture, as well as the amount of deposition on the soil. The study was conducted in the field using the peanut cultivar IAC Tatu-ST and the treatment applications were performed at the vegetative (V1) and reproductive (R2) stages. Brilliant Blue (FD&C-1) was used as tracer in water solution, at 500 ppm. The treatments were constituted of seven spray nozzles: XR 110015 VS (150 L ha-1), XR 11002 VS (200 L ha-1), TX-VK 6 (150 L ha-1), TX-VK 8 (200 L ha-1), AI 110015 VS (150 L ha-1), AI11002 VS (200 L ha-1) and TJ60 11002 VS (150 and 200 L ha-1). A randomized block design was used, with four replications. The results showed that the application of a larger spray volume increased the amount of depositions on the plants IAC Tatu ST at both stages of crop development, with the exception of spray nozzles XR 110015 VS and AI11002 VS, at the vegetative (V1) and reproductive (R2) stages of the culture, respectively; the greatest loss of drops in applications on the soil at the vegetative stage (V1) was provided by the spray nozzles AI 110015 VS and AI 11002 VS; however, at the reproductive stage (R2), the spray nozzle XR 11002 VS caused the greatest loss; The spray nozzles XR 11002 VS, AI 110015 VS, and TJ60 11002 VS (150 L ha-1) provided higher depositions on the leaves of B. plantaginea planted in the row than between the rows in the applications at the vegetative stage (V1), while at the reproductive stage (R2), the spray nozzles showed similar results for the deposition of droplets on the weed.
Quantitative aspects of spray droplet deposition on peanut plants and Brachiaria plantaginea
Keywords: Application technology; Deposition uniformity; Spray nozzle; Weed